Indução de morte celular em células de adenocarcinoma cervical humano (HeLa) pela lectina da esponja Cinachyrella apion (CaL) - Rabelo, Luciana Maria Araújo (2011)
Cancer is a term used to represent a set of more than 100 diseases, including malignant tumors from different locations. The malignancies are the second leading cause of death in the population, representing approximately 17% of deaths of known cause. Strategies that induce differentiation have had limited success in the treatment of established cancers. In this work, a lectin purified from the marine sponge Cinachyrella apion (CaL) was evaluated due to its hemolytic, cytotoxic and antiproliferative properties, besides the ability to induce cell death via apoptosis in tumor cells. The antiproliferative activity of CaL was tested against cell lines, with the highest inhibition of tumor growth for HeLa, reducing cell growth at a dose dependent manner, with a concentration of 10 μg/mL. The hemolytic activity and toxicity against peripheral blood cells were tested using the concentration of IC50 for both trials and twice the IC50 for analysis in flow cytometry, indicating that CaL is not toxic to these cells. To assess the mechanism of cell death caused by CaL in HeLa cells, we performed flow cytometry and western blotting. The results showed the lectin probably induces cell death by apoptosis activation by pro-apoptotic protein Bax, promoting mitochondrial membrane permeabilization, cell cycle arrest in S phase, with accumulation of cells of approximately 57% in this phase, and acting as both dependent and/or independent of caspases pathway. These results suggest that CaL has the potential to be used as drug treatment against cancer.